2021
DOI: 10.3390/publications9040055
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Research in Ecuador: A Bibliometric Analysis

Abstract: Ecuador has shown a growth in its scientific production since 2011, representing 85% of the total historical production. These investigations are reflected in scientific publications, which address world interest topics and serve as a link for the university, business, and society. This work aims to analyze the scientific production generated by Ecuador in the period of 1920–2020 using bibliometric methods to evaluate its intellectual structure and performance. The methodology applied in this study includes: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 284 publications
(294 reference statements)
1
13
0
Order By: Relevance
“…It is important to note that similar observations about the growth of the scientific production of Ecuador were reported and discussed in previous studies, where the scientific articles published in different periods of time (i.e., 1920–2020 in Ref. [ 10 ] and 2006–2015 in Ref. [ 11 ]) were analyzed by means of various bibliometric tools.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…It is important to note that similar observations about the growth of the scientific production of Ecuador were reported and discussed in previous studies, where the scientific articles published in different periods of time (i.e., 1920–2020 in Ref. [ 10 ] and 2006–2015 in Ref. [ 11 ]) were analyzed by means of various bibliometric tools.…”
Section: Introductionsupporting
confidence: 52%
“…On the other hand, COMP is the area with the largest count of authors as well as percentage of permanency, which allows this field to be suggested as one of the most developed ones in Ecuador during the 2001–2020 period as also concluded by Herrera-Franco et al. [ 10 ]. Other fields presenting important percentages of permanency are: NEUR, MATH, DECI, BUSI, VETE, and NURS as obtained for decade-B.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…After we corrected these errors, 396 documents remained. In addition, the software allows analysing the performance of scientific outputs according to various units of analysis, such as documents, authors, countries and journals [70,97]. (ii) VOSviewer: It is an open-access software developed by The Centre for Science and Technology Studies of Leiden University (Netherlands).…”
Section: Phase Iii: Inclusion and Exclusion Criteria For Documents An...mentioning
confidence: 99%
“…According to the QS Latin America University Rankings 2021 [ 51 ], ESPOL is ranked No. 74 among 411 universities in Latin America [ 52 ]. In addition, the Green Metric 2021 [ 53 ] ranks ESPOL as the No.…”
Section: Introductionmentioning
confidence: 99%